Investigation on The Correlation Between The Road Accidents And Driver Behaviours Through Observations And Statistical Analysis Along Batu Pahat – Kluang - Jamaludin, Muhammad Syahrunnizam; Nasradeen Ali Khalifa Milad (Recent Trends in Civil Engineering and Built Environment, 2023)
Batu Pahat – Kluang route has the highest occurrence of accidents in Malaysia. According to Jabatan Siasatan Dan Trafik Bukit Aman, the ADT (Annual Daily Traffic) in 2019 for cars is 36,704 and the most accidents occurred during that year with 573,341. The objective of this study is to investigate the correlation between behaviors and road accidents as well as understanding the patterns of the behavior. By using questionnaires, the data then will be analyzed using parametric methods via SPSS. The highest behavior act by the drivers that were using FT050 route is behavior that related to driving skills and the lowest is the behavior that related to interactions among drivers on the road. Therefore, further research needs to be implemented in order to gain more complex data so that the behavior can be analyzed more accurately and provide future solutions.